The Thyroid "Colloidocystic nodule" as a cytological diagnosis. - Delgado, Bolívar; Yametti, Luis; Farre, Iliana; Risi, Leonardo (Cirugía del Uruguay, 1989)
Authors revise a series of 207 thyroid nodules cytologically studied with hystological control; 129 of these had been informed as colloidocystic nodules.